Implication of manufacturing industries within Langat drainage basin: issues and challengers - Ahmad Fariz Mohamed; Jamaluddin Md.Jahi (Environmental Management Society, Malaysia, 2000)
The sitting of industries has ever since been based on a number of economic theories on industrial for maximization of profits. With growing environmental concerns, the location of industries has started to be questioned since some has adverse implications on ecosystems’ health especially on human comfort and health. Since the 1970’s Malaysia’s industrial growth has increased tremendously and with Vision 2020 it has become the focus of development in this country. In relation to this, Langat Drainage Basin, being in close proximity to the Klang Valley Urban Region has been one of the most developed in terms of industry. Industrial growth within Langat Drainage Basin has triggered growth in other sectors and has increased the general standard of living of the population to be more vulnerable to environmental degradation causing the population to be more vulnerable to environmental risks and hazards. The threat to human health and safety specifically and ecosystem health within the Basin in general is partly due the haphazard sitting and zoning of industries and not complying to the stipulated guidelines. Therefore, it is suggested that industrial discharges should be constantly monitored and the approval of industries in the future should be done in accordance with the guidelines and relevant regulations